Entrepreneurs and economic development: the remarkable story of garment exports from Bangladesh - Quddus, Munir; Rashid, Salim (Dhaka : The University Press Ltd., 2000)
Economics
Keywords: Entrepreneurship; Economic development; Garment exports; Global clothing markets; Garment entrepreneurs